THE RELATIONSHIP BETWEEN LEARNERS’ AUTONOMY AND THEIR ACHIEVEMENT IN LEARNING ENGLISH AT 11TH GRADE OF SMA NEGERI 1 TEMBILAHAN HULU - M. Tomy; Edi Ardian; Agus Mustajib (Program Studi Pendidikan Bahasa Inggris, 2020)
The problem of this research was Learners' achievement seems low, while their autonomy seems higher. The method of this research was quantitative correlation research. Therefore, the purpose of this study was to investigate the correlation between learners' autonomy (Variable X) with learners' achievement (Variable Y). The sample of this study was 145 students of eleventh-grade students of SMAN 1 Tembilahan Hulu. The researcher gave questionnaires of learners' autonomy to collect data and asked the value of their English teacher's achievement. After the data has been collected, it was found that the average of learners' autonomy is 77,9%, it was in the